Do parents Influence the Choice of Tertiary Institutions for their Children? Some Statistical Analyses - Kyei, Kwabena A. (Journal of Economics and Behavioral Studies, 2015)
The paper investigates whether or not parents influence their children’s choice for tertiary institution to attend. Education has increasingly become more important in this present age to the extent that, without higher qualifications, employment and success become very difficult to achieve. Parents are trying to send their children to tertiary institutions so that these children will be employable. But the question is: Do parents choose the tertiary institutions for their children? The paper wants to find out whether or not parents have a say in their children’s choice for tertiary institution; and if so, look at factors that could play in the choice. A survey was conducted at the University of Venda from February 2015 to June 2015 and 500 students were conveniently sampled and interviewed. Using some statistical analyses, including Generalized Linear Modelling (GLM), the study concludes that age and the campus environment are the only factors that determine parents’ influence on their children’s choice for higher education. The study further shows that female students are more influenced by their parents than males in the choice of higher institution.